Accounting basis adjustments and deficit reliability: evidence from southern european countries - Jesus, M. A.; Jorge, S. (Revista de Contabilidad - Spanish Accounting Review, 2016)
Governmental Accounting (GA) and National Accounts (NA) are two reporting systems that, although aiming different purposes, are linked – public administrations’ financial information for the latter is provided by the former. Therefore the alignment between the two systems is an issue to the reliability of the public sector aggregates finally obtained by the National Accounts. In the EU context, this is a critical issue, inasmuch as these aggregates are the reference to monitor fiscal policy underlying the Euro currency. However, while reporting in NA is accrual-based and harmonised under the European System of Regional and National Accounts, regarding GA each country still has its own reporting system, often mixing cash basis in budgetary reporting with accrual basis in financial reporting, hence requiring accounting basis adjustments when translating data from GA into NA. Starting by conceptually analysing the accounting basis differences between GA and NA and the adjustments to be made when translating data from the former into the latter, this paper uses evidence from three southern European countries – Portugal, Spain and Italy, representing the southern Continental European accounting perspective, with cash-based budgetary reporting and where budgetary deficits have been particularly significant in the latest years – to show how diversity and materiality of these adjustments may question the reliability of the budgetary deficits finally reported in NA. Main findings point out to the need of standardised procedures to convert cash-based (GA) into accrual-based (NA) data as a crucial step, preventing accounting management, thus increasing reliability of informative outputs for micro and macro perspectives.